2022
DOI: 10.1021/acscentsci.1c01058
|View full text |Cite
|
Sign up to set email alerts
|

High-Content Imaging Platform to Discover Chemical Modulators of Plasma Membrane Rafts

Abstract: Plasma membrane organization profoundly impacts cellular functionality. A well-known mechanism underlying this organization is through nanoscopic clustering of distinct lipids and proteins in membrane rafts. Despite their physiological importance, rafts remain a difficult-to-study aspect of membrane organization, in part because of the paucity of chemical tools to experimentally modulate their properties. Methods to selectively target rafts for therapeutic purposes are also currently lacking. To tackle these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Curiously, lipids in the formaldehyde vesicles are known to phase separate into microdomains under some conditions. [69][70] Taken together, these results suggest that the physical chemistry of lipids is important for GM1 domain formation that is detectable by fluorescence microscopy. However, the physical chemistry of lipids is not sufficient for lipid domain formation, because the observed GM1 separation occurs exclusively in response to ligand binding to the EphA2 receptor.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Curiously, lipids in the formaldehyde vesicles are known to phase separate into microdomains under some conditions. [69][70] Taken together, these results suggest that the physical chemistry of lipids is important for GM1 domain formation that is detectable by fluorescence microscopy. However, the physical chemistry of lipids is not sufficient for lipid domain formation, because the observed GM1 separation occurs exclusively in response to ligand binding to the EphA2 receptor.…”
Section: Discussionmentioning
confidence: 76%
“…The reason for the observed differences between the two types of vesicles is unknown, but effects of formaldehyde‐induced cross‐linking of vesicle components, and perhaps reduction of some disulfide bonds, may play a role. Curiously, lipids in the formaldehyde vesicles are known to phase separate into microdomains under some conditions [69–70] …”
Section: Resultsmentioning
confidence: 99%
“…Beyond mimicking the cell membrane, phase separation could also be used to engineer stimuli-responsive vesicles to enhance drug delivery. Phase separation can be induced through multiple stimuli including tension, 60 pH, 61 temperature, 62 small molecules, 63 peptides, 64 proteins, 65,66 and association with soluble oligomerizing molecules. 67, 68 Phase-separated vesicles could be used in conjunction with these stimuli to dynamically change the presentation of nanoparticle-bound ligands.…”
Section: Discussionmentioning
confidence: 99%
“…127,128 For instance, Cell Painting, a powerful imaging platform wherein 1500 morphological features of plated cells can be measured, was applied to visualize eight physiologically critical cellular organelles using five fluorescent channels. 129 Fricke et al 130 applied HCS to identify small molecules that promoted or disrupted the organization of cell membranes by regulating lipid rafts. Saha and co-workers applied HCA in tandem with statistical design of experiments to optimize lipofection conditions and concluded that the composition and concentration of transfection reagents were the most critical experimental parameters (Figure 6B).…”
Section: High-throughput Evaluation Of Polymeric Gene Delivery In Cel...mentioning
confidence: 99%
“…The convergence of advanced image informatics algorithms and automated confocal microscopy has led to the development of high content screening (HCS), a powerful multiparametric and high-throughput screening system for in vitro gene delivery. , For instance, Cell Painting, a powerful imaging platform wherein 1500 morphological features of plated cells can be measured, was applied to visualize eight physiologically critical cellular organelles using five fluorescent channels . Fricke et al . applied HCS to identify small molecules that promoted or disrupted the organization of cell membranes by regulating lipid rafts.…”
Section: High-throughput Evaluation Of Polymeric Gene Delivery In Cel...mentioning
confidence: 99%